CuAg bimetallic nanoparticles for the electrochemical reduction of carbon dioxide - Dlamini, Gcinisizwe (Department of Chemical Engineering, 2021)
The electrochemical reduction of carbon dioxide is a surface reaction, involving the conversion of carbon dioxide and water to hydrocarbons and oxygenates in an electrolytic environment. This reaction grants an opportunity for the rerouting of carbon dioxide from expulsion to the atmosphere towards the production of chemical products. Due to the stable C-O bond in carbon dioxide, this reaction requires a catalyst and an external energy source to activate it. The use of renewable energy as an energy source would ensure that the electrochemical reduction process is carbon neutral. Cu has been identified as a promising catalyst for the electrochemical reduction of carbon dioxide, as it is more active and produces higher amounts of hydrocarbons and oxygenates relative to other transition metals,. However, Cu is unselective towards a specific product, and it highly active for the undesirable hydrogen evolution reaction (Kuhl et al., 2014). On the other hand, under electrochemical conditions, Ag yields mainly CO, which has been shown to compete with the hydrogen evolution reaction (Hori, Murata & Takahashi, 1989). This study focuses on the synthesis of different ratios of CuAg bimetallic nanoparticles, and their electrocatalytic performance evaluation for the electrochemical reduction of carbon dioxide. Bimetallic nanoparticles were synthesised via a wet chemical method using two synthesis routes. One synthesis was performed in the presence of hexadecylamine (HDA), surfactant, while the other was performed in its absence. The electrocatalytic performance evaluation was conducted using two reactors, a batch reactor with a gas diffusion electrode, and a rotating disc electrode reactor. It was found that catalysts synthesised in the absence of HDA had a phase-separated atomic arrangement, forming islands of Cu and Ag. On the other hand, synthesis conducted in the presence of HDA culminated in a CuAg solid solution. The two synthesis routes resulted in catalysts that had distinct product distributions. Catalysts prepared in the absence of HDA predominantly formed formate, with catalysts that had a higher Cu content forming methanol and CO. The yield of formate for catalysts synthesised under the absence of HDA did not decline at higher potentials relative to Cu catalysts which suffered from hydrogen production. On the other hand, bimetallic catalysts synthesised in the presence of HDA demonstrated behaviour similar to monometallic catalysts. Catalysts with a higher Cu content predominantly produced formate, while catalysts with a high Ag content produced a CO rich stream. This study indicates a profound dependency of the catalyst activity and product distribution on the CuAg bimetallic ratio and atomic arrangement. This study adds knowledge on the synthesis of CuAg bimetallic nanoparticles, and the design of catalysts for the electrochemical reduction of carbon dioxide.